Buying stolen goods: the ambiguity in trading consumer-to-consumer. Issue 1 (2nd January 2017) - Kammersgaard, Tobias; Heinskou, Marie Bruvik; Demant, Jakob
Abstract: This study investigates the buying of stolen goods in Denmark. The study consists of a self-report survey based on a representative sample of the general Danish population ( n = 2311) and six focus group interviews consisting of both informants experienced with buying stolen goods and of those with no experience ( n = 37). The survey showed that 4.8% had bought stolen goods, while 15.7% were uncertain whether they had bought stolen goods. Young people, males, and unemployed were more likely to purchase stolen goods. No clear correlation between income and buying stolen goods was found. Focus groups suggest the buyers of stolen goods did not buy stolen goods because they could not afford legitimate products. We recommend targeting consumers not interested in buying stolen goods with information about how to avoid such activity.